IoT based brain-wave assistive system for paralyzed individuals - Monowara, Syeda Maliha; Shariar, Md Ahnaf; Islam, Md. Shafayat Ul; Jawad, Muhammed Junaid Noor (BRAC University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2020.